Diseño de una máquina para el proceso de acabado y empaque de aplicadores vaginales para la empresa Dakota Plásticos (2018)
This project seeks to eliminate excess material (burr) present after the manufacture of vaginal applicators by the company Dakota Plásticos Ltda., In turn improving this process is intended to reduce times in the preparation and dispatch of the applicators, since currently the removal of Applicator burr is produced manually. In order to satisfy the needs of the company, the characteristics of the process of finished, so that in this way a possible solution to the problem. Taking into account the information provided by the company and the analysis relevant to the process, three alternative solutions were proposed for the problem, looking in this way for the best option in terms of economy, improvement in product quality and thus meet the objectives posed.